OBTAINING AND TESTING COARSE GRAIN SIZE DISTRIBUTIONS FROM PHOTOGRAPHIC GRID COUNTS - Karalis, S.; Aytousmis, A.; Iordanou, A.; Karakostas, G.; Charatsis, K.; Karymbalis, E. (Bulletin of the Geological Society of Greece, 2016)
The grain size distribution (GSD) of surface bed material in alluvial rivers is of interest in many geological, ecological and engineering applications. In this work, which is a part of our broader Ph.D research in Vouraikos river on sediment transport, we are testing the possibility of obtaining such a distribution from photographs taken at the field (grid sampling), compared with the standard method which is the “pebble count”. We have also examined and quantified the errors resulting from radial distortion of the photographs. The motive of the work was to explore the opportunity of substituting field work for laboratory work. Results show that for this method to give reliable results, a better knowledge of the site-specific conditions is needed, which, in turn, requires more field work.